Clinical outcomes in patients with bicuspid aortic valves and ascending aorta dilatation equal or above 50mm. (3rd October 2022) - Ye, Z; Lane, C; Beachey, J; Medina-Inojosa, J; Galian, L; Dentamaro, I; Calvo-Iglesias, F; Alegret, J; Sanchez, V; Moral, S; Bellino, M; Enriquez-Sarano, M; et al.
Abstract: Background: Little is known about clinical outcomes in patients with bicuspid aortic valve (BAV) and ascending aortic diameters ≥50 mm where the elective surgical-indication zone begins. Purpose: To assess incident aortic dissection (AoD), post-surgical survival and guideline implementation. Methods: Multi-center retrospective study of BAV patients (≥18 years) with maximal root or tubular-ascending aortic diameters ≥50mm detected by transthoracic echocardiography at baseline. Ascertainment of aortic surgery, AoD and death was carried-out at their respective institutions. The primary outcome was AoD: "confirmed" AoD by surgery or death certificate, or "possible" AoD defined as sudden cardiac death of unknown cause by death certificate. Secondary outcomes were aortic surgery, post-surgical survival and guideline implementation. Results: We included 506 consecutive BAV patients, mean age 61±14 years, 83% men, mean maximal aortic diameter 52±2 mm at baseline, ascending aorta was the most common segment ≥50mm (85%). During a median follow-up of 7.7 years, 356 (71%) underwent elective surgery (89% of class 1 patients). Early-surgery (≤6 months from baseline) occurred in 195 patients and 311 patients remained "under-surveillance". Surgery under-surveillance (>6 months from baseline) occurred in 161/311 (52%) patients at 2.6 [IQR: 1.5–4.7] years of follow-up. Surgical mortality was 1.4%. Ten-year post-surgical survival was >90% and similar between early-surgery and surgery under-surveillance (p=0.8). Of 8 AoD events, 3 confirmed and 5 possible (all occurring in unoperated patients under-surveillance), 5 events occurred with maximal aortic baseline diameter ≥55 mm and/or >1 year without clinical follow-up; therefore, under guideline non-compliance. Incidence of confirmed plus possible aortic dissection was 0.37% per year with size 50–54mm, 1.13% per year between 55–59mm, and 10.41% per year with size ≥60mm. Aortic stenosis was associated with AoD (p=0.04) and all-cause death in unoperated patients (p=0.001). Conclusions: Our results suggest that BAV patients can be safely followed as per guidelines after aortic diameters enter the elective surgical zone (≥50mm), with excellent post-surgical survival regardless of whether surgery is early- or under-surveillance. Appropriate guideline implementation for surgical thresholds and interval clinical follow-up could have prevented most AoD events. Valvular disease guideline should also be followed to prevent AoD and improve survival in these patients. Funding Acknowledgement: Type of funding sources: None.